LUKS DATA ENCRYPTION FOR DEVICES USING HARDWARE ANDSOFTWAREFINGERPRINTING - Wahyu Suryo Samudro; Adharul Muttaqin; Angger Abdul Razak (Jurnal Mahasiswa TEUB, 2023)
In this post-era of Covid-19 there are many massive changes to the socio-economic happening around the world, especially when it comes with electronic or computer usage aspects. The lockdown laws and economic recession caused by the Covid-19 forces people to use their current electronic and/or computer for almost all of their lives aspects and because of that many of the personal data stored on their computers. Based on statistics that majority in 2022 still have an security ready computers, indicated by the lack of adoption or 55.6% did not upgrade the popular Computer OS Windows to Windows 11, which notoriously requires security ready equipped devices, and the cons of the lack of security specific feature on the hardware one of them is information sensitive is left unencrypted or user have to manually re-input the authentication that the user have for that information after every computer/electronic boot up. Which lead to this research of using computer identification from combination of hardware and software which creates a SHA512 hash fingerprint where it can be generated upon boot time and no need to persistently stored in an unencrypted form. As proof of concept the it is built on Linux system for easy understanding on how the system works, and tested to be successfully passed 7 out of 7 test points that is being tested. Keywords— LUKS, Fingerprinting, Decryption, Automatic Authentication, Encryption